DEVELOPMENT OF THE PERSPECTIVE REINFORCING MATERIALS FOR CONCRETE ON JSC «BSW – MANAGEMENT COMPANY OF HOLDING «BMC» - T. A. Akhmetov; I. N. Radkova; L. V. Loktionova; Y. V. Chikishev; A. V. Mazanik; L. V. Loktionova (Литьë и металлургия, 2016)
The main stages of establishing and development of manufacture techniques for production of cold-shaped reinforcing steel in reels and a steel fiber in StPTs-3 (innovative processes in the Republic of Belarus) are considered in the article.